Marriage Tradition of Tobati Tribe: in Perspective on Islamic Law - Eko Siswanto; A. Ubaidillah (LPPM IAIN Kudus, 2020)
This study investigated the marriage has human values to fulfill the instincts of human life. In the community of Tobati tribes, marriage has been arranged based on its customary traditions that have been agreed upon for generations. It focused on exploring the form of the marriage tradition of the repentant tribal people and how Islamic law analyzes the similarities and differences. The researcher applied descriptive qualitative design to explore the objectives of this study then analyzed by Miles Huberman’s theory. The findings show that there are several steps in the marriage process, namely: first, propose (ask in marriage); second, waiting for a period (waiting for a decision from the woman’s family); third, giving the application, and the last, the procession of the marriage. These four stages, there are similar to the stages of marriage according to Islamic law, but there is a very significant difference, namely the obligation to deliver the application after obtaining approval to carry out the wedding procession.